Discrimination in a General Algebraic Setting. (1st June 2015) - Fine, Benjamin; Gaglione, Anthony; Lipschutz, Seymour; Spellman, Dennis
Abstract : Discriminating groups were introduced by G. Baumslag, A. Myasnikov, and V. Remeslennikov as an outgrowth of their theory of algebraic geometry over groups. Algebraic geometry over groups became the main method of attack on the solution of the celebrated Tarski conjectures. In this paper we explore the notion of discrimination in a general universal algebra context. As an application we provide a different proof of a theorem of Malcev on axiomatic classes of Ω-algebras.